The wars in Syria and Palestine of Thutmose III - Redford, Donald B. (Culture and history of the ancient Near East, 2003)
In order to subject the Asiatic campaigning of the 15th-century BC Egyptian Pharaoh to new investigation, Redford (classics and ancient Mediterranean studies, Pennsylvania State U.) has assembled, collated, and translated sources and commented on the texts and contents. The wars are the best documented in Egypt's history.